Carbohydrate ligand engagement with CD11b enhances differentiation of tumor-associated myeloid cells for immunotherapy of solid cancers - Mei Zhang; Veronique Roche; Victor Sandoval; Claire Wolford; Zachary Senders; Julian Anthony Kim; Susan Pereira Ribeiro; Alex Yicheng Huang; Rafick-Pierre Sekaly; Joshua Lyons (Journal for ImmunoTherapy of Cancer)
Background Efforts to modulate the function of tumor-associated myeloid cell are underway to overcome the challenges in immunotherapy and find a cure. One potential therapeutic target is integrin CD11b, which can be used to modulate the myeloid-derived cells and induce tumor-reactive T-cell responses. However, CD11b can bind to multiple different ligands, leading to various myeloid cell functions such as adhesion, migration, phagocytosis, and proliferation. This has created a major challenge in understanding how CD11b converts the differences in the receptor-ligand binding into subsequent signaling responses and using this information for therapeutic development.Methods This study aimed to investigate the antitumor effect of a carbohydrate ligand, named BG34-200, which modulates the CD11b+ cells. We have applied peptide microarrays, multiparameter FACS (fluorescence-activated cell analysis) analysis, cellular/molecular immunological technology, advanced microscopic imaging, and transgenic mouse models of solid cancers, to study the interaction between BG34-200 carbohydrate ligand and CD11b protein and the resulting immunological changes in the context of solid cancers, including osteosarcoma, advanced melanoma, and pancreatic ductal adenocarcinoma (PDAC).Results Our results show that BG34-200 can bind directly to the activated CD11b on its I (or A) domain, at previously unreported peptide residues, in a multisite and multivalent manner. This engagement significantly impacts the biological function of tumor-associated inflammatory monocytes (TAIMs) in osteosarcoma, advanced melanoma, and PDAC backgrounds. Importantly, we observed that the BG34-200-CD11b engagement triggered endocytosis of the binding complexes in TAIMs, which induced intracellular F-actin cytoskeletal rearrangement, effective phagocytosis, and intrinsic ICAM-1 (intercellular adhesion molecule I) clustering. These structural biological changes resulted in the differentiation in TAIMs into monocyte-derived dendritic cells, which play a crucial role in T-cell activation in the tumor microenvironment.Conclusions Our research has advanced the current understanding of the molecular basis of CD11b activation in solid cancers, revealing how it converts the differences in BG34 carbohydrate ligands into immune signaling responses. These findings could pave the way for the development of safe and novel BG34-200-based therapies that modulate myeloid-derived cell functions, thereby enhancing immunotherapy for solid cancers.